Development of marked striatal hand with antiparkinsonian medication withdrawal during traditional (Ayurvedic) medicine treatment for Parkinson's disease - Lim, Shen-Yang; Goh, K.J.; Zain, A.A.; Ramli, N.; Choo, Yeun-Mun; Tan, G.H. (Asean Neurological Assoc, 2010)
Ayurveda is a traditional medical system used widely in India and increasingly worldwide. Here, we report on a patient with Parkinson's disease (PD) who developed marked striatal hand with antiparkinsonian medication withdrawal during Ayurvedic medicine treatment for her PD. Although a direct role for the Ayurvedic medicines in inducing the hand deformity cannot be excluded, we propose that severe dopaminergic deficiency (due to prolonged withdrawal of antiparkinsonian medications in the context of long-standing PD) was probably the main culprit in our patient.